Pelatihan Pemanfaatan Media Sosial Sebagai Alat Pemasaran Produk Kampung Akrilik - Ade Irma Suryani; Sri Restu Ningsih; Rahmadini Darwas; Rahimullaily Rahimullaily (Universitas Lancang Kuning, 2022)
PKM partners are product craftsmen in Acrylic Village, which is located on Jalan Gunung Pangilun, North Padang District. The problems that occur in Acrylic Village include (a) the absence of social media facilities to promote handicraft products of acrylic village members (b) The lack of knowledge of the craftsmen of Acrylic Village products on how to promote their products on social media, and (c) the lack of knowledge of craftsmen on how to promote their products. products using digital techniques through Android applications. The solutions to the problems obtained are (a) The implementation of this PKM is expected to be able to hold training in making promotional media for product promotion produced by members in Acrylic Village, (b) It is hoped that social media training for this promotional media can facilitate craftsmen members to be able to make promotional advertisements. handicraft vendors in increasing product sales, (c) Providing knowledge to craftsmen members about the tricks and ways of promoting products on social media using digital techniques in the Android application (d) The results of their creativity, in the form of product photos, can be useful and advertised on social media to increase product sales. The method of implementing the activities includes four stages, namely: program planning, program implementation, observation and evaluation. In program planning, there are several plans that will be carried out, namely (a) Field Study, (b) Training and provision of craftsman group members. (c) Program socialization. (d) Preparation of training programs. In the implementation of the program, (a) Formation of several working groups of craftsmen based on the type of product, (b) Improving the knowledge and skills of the craftsmen to make their own mini studio to make product photos to be marketed, (c) Demonstrating how to use digital techniques on mobile phones and directly practiced, (d) coaching and training in making promotions with social media to increase sales. At the observation stage, what will be done is to see the obstacles, shortcomings and weaknesses that arise in the training process on how and tricks to promote simple acrylic village handicraft products using digital techniques on the Android application.